Mild cognitive impairment and its associated factors amongst the older people attending government health clinics in Kuantan - Roop Kishore, Yashdev Atri; Shalihin, Mohd Shaiful Ehsan; Mohammad Aidid, Edre (Malaysian Medical Association, 2025)
Introduction: Malaysia is undergoing a demographic transition towards an aging population, resulting in an anticipated rise in the number of older individuals at risk of developing dementia. Mild cognitive impairment (MCI) represents an intermediate clinical stage between normal cognition and dementia, characterized by cognitive decline that does not significantly impair daily functional activities. Early detection of MCI is critical, as early-stage interventions and modifications of risk factors can yield promising outcomes. Materials and Methods: This cross-sectional study evaluated the prevalence of MCI and its associated factors among 327 older adults attending healthcare clinics. Data were collected using the Elderly Cognitive Assessment Questionnaire, Geriatric Depression Scale, and Barthel Index. Binary logistic regression analysis was performed to identify significant factors of MCI. Results: The prevalence of MCI in the study population was 18.7%, with the majority demonstrating poor control of comorbid conditions. Significant factors of MCI included being a widower (OR 0.4; 95%CI: 0.18, 0.94), increasing age (OR 0.92; 95% CI: 0.88, 0.97), and having diabetes (OR 3.49; 95% CI: 1.81, 6.73). Conclusion: The findings highlight that a significant proportion of older adults are at risk of progressing to dementia but remain underdiagnosed during the early stages. Optimizing blood sugar control emerges as a crucial strategy to mitigate the progression of MCI to irreversible dementia. Implementation of active cognitive screening programs is essential for early identification and timely intervention.